Beneficial Effect of Intravenous Magnesium Sulphate in Term Neonates with Perinatal Asphyxia - Shakir, Khuzaima; Arif, Ayesha; Maryam, Noor; Tariq, Awais; Jamil, Muhammad Irfan; Arslan, Muhammad; Younus, Mohammad Imran (Indus Journal of Bioscience Research, 2025)
Background: Hypoxic ischemic encephalopathy (HIE) is a significant contributor to neonatal morbidity and mortality. This study evaluated the clinical impact of intravenous magnesium sulphate in term neonates with HIE. Methods: A descriptive case series was conducted at the Department of Pediatrics, Jinnah Hospital Lahore, from March 1, 2025 to June 01, 2025. One hundred thirty-eight term neonates meeting diagnostic and severity criteria for HIE were enrolled. Severity was assessed using the Thomson score. All neonates received standard intensive care and intravenous magnesium sulphate at 250 mg/kg over 30 minutes on admission, with repeat doses at 24 and 48 hours. Outcomes were monitored over a 7-day period, including return to normal neurological status, seizure occurrence, establishment of suck feeding, and mortality. Data were analyzed using SPSS version 22. Results: The mean gestational age was 38.4 ± 1.1 weeks, with a mean birth weight of 2985 ± 355 grams. Of the 138 neonates, 82 (59.4%) were male and 56 (40.6%) were female; 44 (31.9%) had HIE grade I, 70 (50.7%) grade II, and 24 (17.4%) grade III. Following therapy, the mean Thomson score decreased from 13.1 ± 2.9 to 1.5 ± 1.2 by day 7. Return to normal neurological status was documented in 101 (73.2%) neonates. Seizure activity occurred in 36 (26.1%). The ability to establish effective suck feeding by day 7 was achieved in 110 (79.7%) neonates. Mortality within seven days was observed in 12 (8.7%) cases. Conclusion: The addition of intravenous magnesium sulphate to standard management was associated with substantial neurological recovery, improved feeding outcomes, and low short-term mortality in term neonates with HIE.